2021
DOI: 10.12688/f1000research.53506.2
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing COVID-19 vaccine acceptance in Indonesia: an adoption of Technology Acceptance Model

Abstract: Background: It is critical to understand the factors that could affect the acceptance of the coronavirus disease 2019 (COVID-19) vaccine in the community. The aim of this study was to determine factors that could possibly affect the acceptance of Indonesian citizens of COVID-19 vaccination using a Technology Acceptance Model (TAM), a model how users come to accept and use a technology. Methods: An online survey was conducted between the first and fifth of November, 2020. Participants were asked to respond to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“… 24 Studies from the Philippines and Indonesia revealed that perceptions of being susceptible and having more severe disease after being infected and perceived efficacy and benefits of the COVID-19 vaccines were predictors for vaccine acceptance. 21 , 25 Studies in Bangladesh, Pakistan and the United Arab Emirates also showed similar patterns. Among university students in Bangladesh, those without a previous COVID-19 infection, poorer knowledge related to COVID-19, and negative perceptions and attitudes toward the vaccine were significantly associated with vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“… 24 Studies from the Philippines and Indonesia revealed that perceptions of being susceptible and having more severe disease after being infected and perceived efficacy and benefits of the COVID-19 vaccines were predictors for vaccine acceptance. 21 , 25 Studies in Bangladesh, Pakistan and the United Arab Emirates also showed similar patterns. Among university students in Bangladesh, those without a previous COVID-19 infection, poorer knowledge related to COVID-19, and negative perceptions and attitudes toward the vaccine were significantly associated with vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 59%
“…A study in Indonesia also revealed that the perceived effectiveness and ease of to access the vaccine, rather than their religious belief, influenced their vaccine acceptance. 21 Domestic helpers in Hong Kong were concerned about the local transmission risks, their family members’ health conditions and financial demands in their home country, changes to how their employers treated them, their employment status, and a lack of support from the Hong Kong Government. This “dual-country experience” encountered by domestic helpers in Hong Kong during the COVID-19 pandemic could have influenced their willingness to be vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…The negative attitudes may have been related to the report on Sinovac's clinical trial, which provided conflicting results in some countries (18), which potentially causing confusion and public distrust. In addition, it may also be possible that this vaccine remain offensive to the interplay between religion beliefs, politics, and personal beliefs that influence individual and community decision around vaccination (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to cultural diversity, each country might have a different level of acceptance and associated determinants. A previous study revealed that religiosity was an essential determinant influencing parents' approaches to health management issues (19,21). Thus, the Indonesian government or other related organizations should focus on providing information regarding the benefits of vaccination to the community and ensure that the vaccines are easily accessible (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation